Assembly, Disassembly and Reassembly of Complex Coacervate Core Micelles with Redox‐Responsive Supramolecular Cross‐Linkers. Issue 4 (27th January 2020) - Facciotti, Camilla; Saggiomo, Vittorio; Bunschoten, Anton; ten Hove, Jan Bart; Rood, Marcus T. M.; van Leeuwen, Fijs W. B.; Velders, Aldrik H.
Abstract: Polymer‐based micellar assemblies are gaining increasing attention in the smart materials field, yet the design of micelles that show redox‐responsive disassembly and, e. g., cargo release is still a challenge. To form redox‐responsive micelles, we developed cyclodextrin‐based coacervate core micelles that form under interplay of four orthogonal interactions: multivalent electrostatic coacervation, metal‐to‐ligand coordination chemistry, supramolecular host‐guest interactions, and a reversible covalent disulfide metal‐complex crosslinker. The cleavage of this crosslinker by dithiotreithol results in the breaking of oligomeric europium(III) structures in the core and results in the disassembly of the 70 nm size micelles. Over hours, due to the oxidation of thiolates to disulfides, monomeric units can re‐crosslink into oligomeric core‐units, favoring micellar reassembly. The time required to reassemble can be controlled by varying the reducing agent concentration or the ratio between redox‐responsive and non‐redox‐responsive crosslinkers. Controlled Methyl Red encapsulation and release indicate the potential of these micelles, for, e. g., controlled drug uptake and delivery. Abstract : Make and break : Four orthogonal interaction motifs, electrostatic coacervation, metal‐to‐ligand coordination, host‐guest interactions and reversible disulfide bonds used as crosslinkers, are used to form redox‐responsive micelles. The cleavage of the disulfide crosslinker by a reducing agent results in the breaking of the oligomeric metal complexes in the core of the micelle and the concomitant disassembly of the latter. Over hours, due to oxidation of thiolates to disulfides, the reformed crosslinkers favor formation of oligomeric complexes that can reform the core of micelles.